2018
DOI: 10.1111/acel.12779
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E region molecular signatures of Alzheimer's disease

Abstract: SummaryAlthough the APOE region is the strongest genetic risk factor for Alzheimer's diseases (ADs), its pathogenic role remains poorly understood. Elucidating genetic predisposition to ADs, a subset of age‐related diseases characteristic for postreproductive period, is hampered by the undefined role of evolution in establishing molecular mechanisms of such diseases. This uncertainty is inevitable source of natural‐selection–free genetic heterogeneity in predisposition to ADs. We performed first large‐scale an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 53 publications
4
31
0
Order By: Relevance
“…Therefore, it should be noted that despite a major impact of the APOE genotypes on the associations of other SNPs inside the chromosome 19q13 region with AD, this result would not automatically imply that the APOE SNPs (i.e., rs429358 and rs7412) are the only contributors to AD pathogenesis because APOE -adjusted models highlighted the statistical correlations rather than biological (i.e., genetic) linkage. Further analyses such as those examining the role of haplotypes and epistatic interactions would be helpful to more comprehensively dissect the genetic heterogeneity of this region, and to elucidate the biological relevance of the APOE -adjusted models [70].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it should be noted that despite a major impact of the APOE genotypes on the associations of other SNPs inside the chromosome 19q13 region with AD, this result would not automatically imply that the APOE SNPs (i.e., rs429358 and rs7412) are the only contributors to AD pathogenesis because APOE -adjusted models highlighted the statistical correlations rather than biological (i.e., genetic) linkage. Further analyses such as those examining the role of haplotypes and epistatic interactions would be helpful to more comprehensively dissect the genetic heterogeneity of this region, and to elucidate the biological relevance of the APOE -adjusted models [70].…”
Section: Resultsmentioning
confidence: 99%
“…PVRL2 ( p -value 4.92 ∗ 10ˆ–34 in Brain (CMC) RNA-seq, also known as NECTIN2) is a well-known gene for AD. This gene encodes a single-pass type I membrane glycoprotein and interact with AOPE gene (Kulminski et al, 2018). TOMM40 [ p -value 1.13 ∗ 10ˆ–25 in Whole Blood (YFS) RNA Array] is also located adjacent to APOE.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the strong LD between variants of the two genes at this locus, we were unable to statistically distinguish the effects of TOMM40 ‐L and APOE ‐ε4 in our series. It has recently been reported that LD structures of genes in the APOE / TOMM40 locus are highly heterogeneous, with significant differences between patients with AD and unaffected controls and that these differing patterns may correspond to heterogenous “molecular signatures” that may denote polygenetically enhanced susceptibility to AD and related diseases [39]. Future work needs to further assess the clinical discriminative value of either variant to distinguish DLB with versus without concomitant AD pathology and to clarify the molecular mechanisms underlying the association between DLB+AD and APOE ‐ε4 or TOMM40 ‐L (or both).…”
Section: Discussionmentioning
confidence: 99%